2019
DOI: 10.1111/pde.13871
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of PHACE syndrome: A survey of adults with PHACE

Abstract: Background Awareness of PHACE syndrome has increased; however, little information exists regarding its natural history, especially in patients over the age of 18. We aim to describe the natural history of PHACE to enhance clinical management and counseling of patients. Methods A cohort of patients ≥ 18 years was identified through the PHACE Syndrome Registry and a Vascular Anomalies Clinic Database. A cross‐sectional survey was designed after a review of the literature by PHACE experts (IF, JP, DS). Questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In our population, four patients underwent surgery, of which three were initially treated with steroids, delaying the introduction of propranolol. In Stefanko's survey of adults with PHACES, 24 50% of the 24 patients examined had undergone numerous laser treatments, which is quite consistent with our study. However, 44% of patients in their study had at least one plastic surgery performed, far higher than observed in our population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our population, four patients underwent surgery, of which three were initially treated with steroids, delaying the introduction of propranolol. In Stefanko's survey of adults with PHACES, 24 50% of the 24 patients examined had undergone numerous laser treatments, which is quite consistent with our study. However, 44% of patients in their study had at least one plastic surgery performed, far higher than observed in our population.…”
Section: Discussionsupporting
confidence: 91%
“…In 2019, Stefanko et al 24 . published the first survey of adults with PHACES syndrome, including 18 patients ranging from 18 to 59 years of age.…”
Section: Discussionmentioning
confidence: 99%
“… 2 As existing PHACE cohorts reach adolescence and adulthood, these complications of PHACE are increasingly being recognised and include migraine-like headaches, 3 TIAs, AIS, 7 MMV 4 and rarely arterial dissection. 5 Although we know patients are at increased risk of these emerging neurovascular-related morbidities, very little is known about the nature of the arteriopathy (ie, no good imaging and no pathology).…”
Section: Discussionmentioning
confidence: 99%
“… 1 Cerebral and cervical arterial abnormalities are the most common non-cutaneous anomaly in PHACE syndrome occurring in over 85% of patients, including vessel narrowing, dysgenesis, anomalous course and/or origin, and non-visualisation. 2 These neurovascular anomalies predispose infants and children to highly morbid complications including headaches, 3 moyamoya vasculopathy (MMV), 4 arterial dissection, 5 6 transient ischaemic attacks (TIAs) and arterial ischaemia stroke (AIS). 7 While there is anecdotal evidence that progressive vascular narrowing and vessel wall abnormalities may be a factor in these neurovascular complications, no study or case report to date has characterised the vessel wall in PHACE syndrome, specifically not in a case of PHACE syndrome with documented, progressive vascular stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study did not distinguish between the experience of the transgender participant and other participants. 67…”
Section: Epilepsymentioning
confidence: 99%